Incorporation of olive pomace ingredients into yoghurts as a source of fibre and hydroxytyrosol: antioxidant activity and stability throughout gastrointestinal digestion - Ribeiro, Tânia B. (2021)
Liquid-enriched powder (LOPP) and pulp-enriched powder (POPP) obtained from olive pomace were incorporated into yoghurt, not only, to increase its content in dietary fibre, hydroxytyrosol and unsaturated fatty acids, but also to understand the lipids-phenolics interaction by simultaneous incorporation of olive oil. POPP (2%) and LOPP (1%) addition to yoghurt allowed fulfilling the condition of being a “source of fibre” and provided 5 mg of hydroxytyrosol and derivatives in a standard yoghurt (120 g), respectively. Yoghurts’ unsaturated fatty acids profile was positively influenced by the addition of only POPP and olive oil + LOPP or + POPP. All OP powder-fortified yoghurts exhibited higher total phenolic content and antioxidant activity than the control (p<0.05). After in vitro digestion the bioaccessibility of total phenolics (more 25.58%) and hydroxytyrosol (more 68.71%) in LOPP-yoghurts was improved by the addition of olive oil. In conclusion, OP powders´ incorporation gave additional and essential healthy properties to yoghurt.